2021
DOI: 10.3889/oamjms.2021.5852
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of FoxO3a Predict the Failure of Imatinib Mesylate Therapy among Chronic Myeloid Leukemia Patients

Abstract: INTRODUCTION: Forkhead Transcription Factor 3a (FoxO3a) has been proposed to have a high efficacy to predict the failure of imatinib mesylate (IM) therapy among Chronic Myeloid Leukemia (CML) patients. However, the limited evidence had made this marker remained controversy. OBJECTIVES: We aimed to investigate the correlation between the levels of FoxO3a and the risk of treatment failure of IM therapy in CML patients. METHODS: A prospective cohort study was carried out between February 2019 and Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…They found that elevated levels of FOXO3a was associated with treatment failure of CGL patient treated with imatinib mesylate, suggesting that the levels of FOXO3a might play an important role to contribute the progression of CGL. 16 Furthermore, studies also found that elevated levels of FOXO3a was associated with adverse prognosis of leukemia. 24,25 However, geneenvironment interaction should also be considered to affect the disease progression since it was proven that the FOXO transcription factors had various impact in different population, for example: the role of FOXO transcription factors were found inconclusive to affect the human longevity in the population of Japan, Germany, Italia, and Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that elevated levels of FOXO3a was associated with treatment failure of CGL patient treated with imatinib mesylate, suggesting that the levels of FOXO3a might play an important role to contribute the progression of CGL. 16 Furthermore, studies also found that elevated levels of FOXO3a was associated with adverse prognosis of leukemia. 24,25 However, geneenvironment interaction should also be considered to affect the disease progression since it was proven that the FOXO transcription factors had various impact in different population, for example: the role of FOXO transcription factors were found inconclusive to affect the human longevity in the population of Japan, Germany, Italia, and Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded from our study if they had a history of the following conditions: prostate cancer, gynecological cancer, COPD, breast cancer, vitiligo, and thyroid cancer. 16 Our present study was conducted following the ethics code of the Helsinki Declaration and was registered and approved by the Ethical Committee of Universitas Brawijaya (No. 400/098/k.3/302/2019).…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…They found that elevated levels of FOXO3a was associated with treatment failure of CGL patient treated with imatinib mesylate, suggesting that the levels of FOXO3a might play an important role to contribute the progression of CGL. 16 Furthermore, studies also found that elevated levels of FOXO3a was associated with adverse prognosis of leukemia. 24 , 25 However, gene – environment interaction should also be considered to affect the disease progression since it was proven that the FOXO transcription factors had various impact in different population, for example: the role of FOXO transcription factors were found inconclusive to affect the human longevity in the population of Japan, Germany, Italia, and Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded from our study if they had a history of the following conditions: prostate cancer, gynecological cancer, COPD, breast cancer, vitiligo, and thyroid cancer. 15 Our present study was conducted following the ethics code of the Helsinki Declaration and was registered and approved by the Ethical Committee of Universitas Brawijaya (No. 400/098/k.3/302/2019).…”
Section: Study Design and Patientsmentioning
confidence: 99%